PENGARUH PERSEPSI TATA KELOLA DAN KARAKTERISTIK PERUSAHAAN TERHADAP RISK-TAKING BEHAVIOR INVESTOR DI PASAR SAHAM - Wiwit Widyawati; Triyono Triyono (Jurnal Riset Akuntansi dan Keuangan, 2014)
This study examines the relationship between the corporate governance perception index and firm characteristics are proxied by institutional ownership , profitability (ROA), growth opportunities (growth sales) and size on the risk-taking behavior judged by market stock returns. The population are company that list in Indonesian Stock Exchange (IDX) and Indonesian Institute for Corporate Governance (IICG) from 2006-2012. Sample was collected based on purposive sampling and resulted in 91 companies as a final sample. Data was collected from Indonesian Capital market Directory (ICMD) and The Indonesian Institute for Corporate Governance (IICG). Its was analyzed with multiple regression analysis. The results indicated that corporate governance perception index, institutional ownership, growth sales and size have significant effect on investor’s risk-taking behavior. But ROA does not impact on investor’s risk-taking behavior. Keywords : corporate governance perception index, firm’s characteristic, risk-taking behavior.